2016
DOI: 10.4314/tjpr.v15i5.27
|View full text |Cite
|
Sign up to set email alerts
|

Natural plant polyphenols for alleviating oxidative damage in man: Current status and future perspectives

Abstract: The balance between oxidation and reduction is important for maintaining a healthy biological system. Oxidative stress results from an imbalance between excessive formation of reactive oxygen species (ROS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 74 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…Natural phenolic compounds have beneficial effects on human health by protecting against oxidative stress-related chronic diseases [ 35 ]. Recent studies reported that phenolic extracts derived from rice bran have anti-oxidant potential by upregulating the expression of nuclear factor erythroid 2–related factor 2 (Nrf2) under oxidative stress conditions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural phenolic compounds have beneficial effects on human health by protecting against oxidative stress-related chronic diseases [ 35 ]. Recent studies reported that phenolic extracts derived from rice bran have anti-oxidant potential by upregulating the expression of nuclear factor erythroid 2–related factor 2 (Nrf2) under oxidative stress conditions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that by-products of oxygen metabolism produce free radicals such as reactive oxygen and nitrogen species which results to cellular damage and pathogenesis of several diseases such as cancer, cardiovascular diseases, diabetes, neurodegenerative diseases among others (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of phenolic compounds from medicinal plants as supplement in the treatment of oxidative stress and free radicals mediated tissue damage cannot the overemphasized (Li et al, 2016). Flavonoids and phenolic acids from polyphenols have been reported to play a significant role in scavenging free radicals and prevention of oxidative damage to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds including flavonoids form the large group of secondary metabolites, exhibits various structures that make them major contributors to the overall pharmacological potentials like antioxidant and antimicrobial activities of many plants [15][16][17][18]. In this context, it was reasonable to assess the total phenolic (TPC) and flavonoid (TFC) contents of the extracts as well as their antioxidant and antimicrobial activities.…”
Section: Discussionmentioning
confidence: 99%